Reproductive atterns of Pollicipes pollicipes (Cirripedia: Scalpellomorpha) on the southwestern coast of Portugal - Cruz, Teresa (2012)
The brooding period of Pollcipes pollicipes on the southwestern coast of Portugal in 1991 began in MArch and extended to October, and was more intense from April to September.